Key to Plecoptera nymphs from the Brazilian Amazon (Insecta) - Ribeiro, José Moacir Ferreira; Gorayeb, Inocêncio De Sousa (Zootaxa, 2016)
Nymphs of 22 species of Plecoptera from the Brazilian Amazon are keyed and illustrated to enhance their usefulness as water quality indicator taxa. Four described species of Anacroneuria, two species of Macrogynoplax, and two species of Enderleina have been associated with adults: Anacroneuria marlieri, A. manauensis, A. minuta, A. singularis, M. delicata, M. pulchra, E. froehlichi, and E. flinti. Nymphs of 14 additional morphospecies not yet associated with adults are included. Characters of the head, pronotum, mesonotum, and metanotum are used to distinguish late instar nymphs.